Partidos, sindicatos e movimentos sociais nos anos 1950-64: balanço histórico-bibliiográfico prelliminar - Lovatto, Angélica [UNESP] (My University, 2011)
This text presents the first results of including research, in process, that it intends to investigate - in the period from 1950 to 1964 - the picture of the progressive political parties, the unions of the city and of the field, and the social movements marked by the national statement and for the anti-imperialism, especially those linked to the world labor perspective, discussing their proposals, differences, performances and commitments due to the political-cultural effervescence of this historical moment.

O presente texto apresenta os primeiros resultados de pesquisa, em andamento, que pretende investigar – no período de 1950 a 1964 – o quadro dos partidos políticos progressistas, os sindicatos da cidade e do campo, e os movimentos sociais marcados pela afirmação nacional e pelo antiimperialismo, especialmente aqueles ligados à perspectiva do mundo do trabalho, discutindo suas propostas, diferenças, atuações e compromissos diante da efervescência político-cultural daquele momento histórico.